PERANAN BUDAYA ORGANISASI DAN KECERDASA EMOSIONAL DALAM MEMPENGARUHI SIKAP TERHADAP PERUBAHAN (STUDI KASUS PADA DOSEN UNIVERSITAS JENDERAL SOEDIRMAN) - Eling Purwanto Jati; Siti Zulaikha Wulandari (Faculty of Economics and Business Universitas Jenderal Soedirman, 2011)
Given the universities strategic significance in producing qualified human resources, the government issued various policies and legislation aimed at improving the performance of universities. Changes in the status of higher education raises individual attitudes or reactions with the level of support varies. This study intends to investigate the influence of Unsoed lecturer’s Emotional Intelligence and Organizational Culture on attitude toward change, and to explores the variable most influencing it and to know the opinion of lecturers to the changes occured in Unsoed and cancellation of BHP Law. Target population in this study were 1.019 Unsoed lecturers, spread in 8 faculties. The sample size was set at 100 respondents, drawn by accidental sampling. By using multiple regression analysis, obtained findings support the hypotheses, which states that Emotional Intelligence and Organizational Culture has a significant influence on Attitude toward Change. Elasticity test results show that Emotional Intelligence has a greater influence than the Organization Culture. Unsoed Lecturers always ready in facing any changes, provided that it has specific and clear goals and should be well socialized to all academic faculty. Most of lecturers had agreed to the cancellation of BHP Law for many reasons such as : Unsoed not ready yet to become BHP (from the financial aspects, organizational structure and human resources perspectives) and BHP will provide a greater opportunity for the communities to get higher education.